Practising teaching using virtual classroom role plays - Dalgarno, B.; Gregory, S.; Reiners, Torsten; Knox, V. (Social Science Press, 2016)
Practice in the role of the teacher is an essential part of teacher education, however professional experience placements are becoming increasingly difficult to find. Consequently, additional university-based teaching practice, such as classroom role play with student teacher peers is important. Classroom role plays can be effective but there are limits to the realism of the experience and such strategies are not feasible for students studying at a distance. This article reports on a study in which a classroom in the virtual world of Second Life was used to house role plays of student teachers in preparation for their first professional experience placement. Based on the results of this study it is concluded that teaching practice using a virtual classroom shows promise but there are a number of usability and other issues which need to be resolved before it will be viewed as an effective strategy by all student teachers.